2016
DOI: 10.3390/nu8100586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 12-Week Vitamin D Supplementation on 25[OH]D Status and Performance in Athletes with a Spinal Cord Injury

Abstract: (1) Background: studies with able-bodied athletes showed that performance might possibly be influenced by vitamin D status. Vitamin D seems to have a direct impact on neuromuscular function by docking on vitamin D receptors in the muscle tissue. Additionally, a high prevalence of vitamin D deficiency was shown not only in infants and in the elderly but also in healthy adults and spinal cord injured individuals. Therefore, the aim of our study was to investigate whether a vitamin D dose of 6000 IU daily over 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 45 publications
3
37
0
1
Order By: Relevance
“…Spinal cord injury (SCI) is one of the most common injuries that requires spinal surgery (1). SCI is often caused by traffic accidents, falls, construction accidents and sports injuries (1). The incidence of SCI has increased with urban and transportation development (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury (SCI) is one of the most common injuries that requires spinal surgery (1). SCI is often caused by traffic accidents, falls, construction accidents and sports injuries (1). The incidence of SCI has increased with urban and transportation development (1).…”
Section: Introductionmentioning
confidence: 99%
“…SCI is often caused by traffic accidents, falls, construction accidents and sports injuries (1). The incidence of SCI has increased with urban and transportation development (1). Recent epidemiological studies have suggested that 11,000 new cases of SCI are reported each year in the USA (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that administration of either of the two regimens for at least 1 month did not cause any adverse effects. Although we cannot exclude that deleterious effects may occur over time, studies done in adults with chronic SCI failed to report any toxicity with larger doses and over longer periods than those tested in this study [13,14].…”
Section: Discussionmentioning
confidence: 66%
“…Although people with SCI are at high risk of impaired vitamin D status, the Endocrine Society clinical practice guidelines on vitamin D have not included explicit population-specific recommendations [11]. Furthermore, only a few repletion protocols have been tested in adults with SCI with varying degrees of improvement [12][13][14][15]. However, most of these studies have been performed in adults with chronic SCI and information regarding vitamin D supplementation strategies shortly after an initial SCI is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, also concluded that the correlation of injuries to vitamin D levels in human body is unclear [19]. Another study evaluated the effect of vitamin D in wheelchair injured athletes and the results support the unclear association of vitamin D with injuries [21]. Nevertheless, a study evaluated Vitamin D status and biomarkers of inflammation in runners and supported a possible link between decreased vitamin D status and one particular marker of inflammation [46].…”
mentioning
confidence: 99%